Root Hair Development in the Grasses: What We Already Know and What We Still Need to Know - Marzec, Marek (Plant Physiol, 2015)
A priority in many crop improvement programs for a long time has been to enhance the tolerance level of plants to both abiotic and biotic stress. Recognition that the root system is the prime determinant of a plant’s ability to extract both water and minerals from the soil implies that its architecture is an important variable underlying a cultivar’s adaptation. The density and/or length of the root hairs (RHs) that are formed are thought to have a major bearing on the plant’s performance under stressful conditions. Any attempt to improve a crop’s root system will require a detailed understanding of the processes of RH differentiation. Recent progress in uncovering the molecular basis of root epidermis specialization has been recorded in the grasses. This review seeks to present the current view of RH differentiation in grass species. It combines what has been learned from molecular-based analyses, histological studies, and observation of the phenotypes of both laboratory- and field-grown plants.